please help me the last person who answered this didn’t get it right so please help:(
![please help me the last person who answered this didnt get it right so please help class=](https://us-static.z-dn.net/files/d4b/c0d48faeaaa77b1d8051e76c3c9bd4eb.png)
Answer:
8
Step-by-step explanation:
3 + [2 + 4(-3)] ÷ (-2)
Following the PEMDAS order of operations, you must start with the terms within the parenthesis/brackets.
= 3 + [2 + (-12)] ÷ (-2)
= 3 + [-10] ÷ (-2)
= 3 - 10 ÷ (-2)
Divide 10 and (-2) by applying the rule: m ÷ ( - n ) = - m ÷ n
= 3 - 10 ÷ 2
= 3 - (-5)
= 3 + 5
= 8
Therefore, the correct answer is 8.
Please mark my answers as the Brainliest if you find my solutions/explanations helpful :)